DOCUMENTARY ANIMATION OR ANIMATED DOCUMENTARY? REFLECTIONS ON THE HISTORY AND THE CURRENT SITUATION ON THE EXAMPLE OF POLAND AND OTHER COUNTRIES / ДОКУМЕНТАЛЬНАЯ АНИМАЦИЯ ИЛИ АНИМАЦИОННАЯ ДОКУМЕНТАЛИСТИКА? РАЗМЫШЛЕНИЯ ОБ ЕЕ ИСТОРИИ И СОВРЕМЕННОЙ СИТУАЦИИ НА ПРИМЕРЕ ПОЛЬШИ И ДРУГИХ СТРАН - VIREN DENIS G. / ВИРЕН Д.Г. (Наука телевидения, 2021)
Documentary animation is a hybrid cinematic form, the history of which goes back over 100 years. Earlier such films were rather a rarity, while lately they appear on screens more and more often. Using numerous examples, the article discusses the goals of artists turning to this unusual and controversial practice. The main thematic blocks are highlighted, the boundaries between the fictional artistic world and the real basis of a film are determined. The author also attempts to distinguish between animated documentary and “full-fledged” documentary animation. After reviewing the genesis (films by W. McCay, J. and F. Hubley) and films that have become modern classics of the direction (Waltz with Bashir, Crulic: The Path to Beyond etc.), the most notable modern samples—primarily those filmed in Poland and in Russia, where animadoc is rapidly gaining momentum—were analyzed in detail. Directors use this form when talking about historical events (reconstruction), ambiguous personalities and unusual places, as well as about their own or others’ internal problems and experiences. Documentary animation is becoming a common means of (auto)psychotherapy and fits into the current trend of pronouncing taboo topics and working out hidden traumas. Animation allows to penetrate deeply into the world of characters without violating their personal boundaries. An important place is held by metafilms, reflecting on the language of the animadoc and cinema in general. Today, documentary with the use of animation is more common than “real” animadoc, although the line between the fictional artistic world and the actual basis of films is rather fluid. The phenomenon is still in the making. Nevertheless, such films must have a real component: interviews (usually off-screen), newsreels, photographs, genuine objects, etc. The factual basis is not a sufficient argument to classify the work as a documentary animation—the decisive factor here is the hybridization of the form. Документальная анимация — гибридная кинематографическая форма, история которой насчитывает более 100 лет, и, если раньше такие фильмы были, скорее, редкостью, в последнее время они все чаще появляются на экранах. В статье на большом количестве примеров рассматриваются цели обращения художников к этой необычной и дискуссионной практике. Выделены основные тематические блоки, определяются границы между вымышленным художественным миром и реальной основой картин. Кроме того, сделана попытка разделения анимационной документалистики и «полноценной» документальной анимации. После рассмотрения генезиса (фильмы У. Маккея, Д. и Ф. Хабли) и фильмов, ставших современной классикой направления («Вальс с Баширом», «Крулик — дорога в загробную жизнь» и др.), подробно проанализированы наиболее заметные современные образцы, прежде всего, снятые в Польше, а также в России, где анимадок стремительно набирает обороты. Режиссеры используют данную форму при рассказе об исторических событиях (реконструкция), неоднозначных личностях и необычных местах, а также о собственных или чужих внутренних проблемах и переживаниях. Документальная анимация становится распространенным средством (авто)психотерапии и вписывается в актуальный тренд проговаривания табуированных тем и проработки скрытых травм. Анимация позволяет глубоко проникнуть в мир героев, не нарушая их личных границ. Важное место занимают также метафильмы, рефлексирующие по поводу языка анимадока и кино в целом. Сегодня документалистика с использованием анимации встречается чаще, чем анимадок, хотя грань между вымышленным художественным миром и реальной основой картин весьма подвижна. Явление по-прежнему находится в процессе становления. Тем не менее в фильмах обязательно должна присутствовать реальная составляющая, будь то интервью (как правило, звучащее за кадром), хроникальная съемка, фотографии, подлинные объекты и т.п. Фактическая основа не является достаточным аргументом для причисления произведения к направлению документальной анимации — решающим фактором здесь становится гибридность формы.